2008
DOI: 10.1007/s00432-008-0463-6
|View full text |Cite
|
Sign up to set email alerts
|

Four consecutive multicenter phase II trials of adjuvant chemoradiation in patients with completely resected high-risk gastric cancer: the experience of the German AIO/ARO/CAO group

Abstract: Adjuvant radiochemotherapy in patients with gastric cancer can be safely given continuous infusion of 5-FU at 225 mg/m(2) per day. In addition, a variety of 5-FU-based multiagent chemotherapy regimen with defined activity in gastric cancer appears both safe and effective when given prior and after radiochemotherapy in this setting.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 31 publications
1
4
0
Order By: Relevance
“…10 As some other authors, we may also conclude that the combined radiotherapy and chemotherapy with 5-FU is feasible, with acceptable toxicity, and seems to have a potential to improve treatment outcome compared to surgery as the sole mode of treatment for this poor prognosis group of patients. [5][6][7][8][9][10][11][12][13][14][15] After a longer follow-up, excellent LRC and acceptable DFS, DSS and OS were confirmed, which concurs with the results from other studies. 5,6,8,9,11,13,23 In the present analysis, the patients with more advanced tumors, cardia involvement, perineurial and vascular invasion had poorer survival.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…10 As some other authors, we may also conclude that the combined radiotherapy and chemotherapy with 5-FU is feasible, with acceptable toxicity, and seems to have a potential to improve treatment outcome compared to surgery as the sole mode of treatment for this poor prognosis group of patients. [5][6][7][8][9][10][11][12][13][14][15] After a longer follow-up, excellent LRC and acceptable DFS, DSS and OS were confirmed, which concurs with the results from other studies. 5,6,8,9,11,13,23 In the present analysis, the patients with more advanced tumors, cardia involvement, perineurial and vascular invasion had poorer survival.…”
Section: Discussionsupporting
confidence: 87%
“…[2][3][4] A number of studies have been conducted to improve the treatment outcome of these patients and, as a result, postoperative radiochemotherapy was established as a routine treatment in the USA as well as in other countries. [6][7][8][9][10][11][12][13][14][15][16][17] The authors believe that the INT 0116 protocol is safe and acceptable for clinical use. 3,5,[8][9][10][11] Data on late side effects are scarce.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, acute side effects were an important concern in the INT-0116 trial, in which 49.1% of the patients experienced National Cancer Institute-Common Toxicity Criteria grade 3 or worse toxicity (9). On the contrary, several more recent studies found the combined modality treatment to be relatively well tolerated (26)(27). Although we cannot rule out poor treatment tolerability as a reason behind the limited use of adjuvant RT, the results of this study point to a partial conclusion: at the very least, poor tolerability is not the sole reason.…”
Section: Discussionmentioning
confidence: 99%
“…First, with the exception of a single phase III study, by Di Costanzo et al [7], and a single randomized phase II trial, by Oechsle et al [8], all studies were phase I or II trials or, more commonly, retrospective analyses. Secondly, aside of the randomized studies described, the retrospective analysis by Kim et al [9] and the current study, all other studies included only a few dozens of patients each.…”
Section: Discussionmentioning
confidence: 99%